IMPLEMENTASI PROGRAM CSR PT PELINDO REGIONAL III SUB REGIONAL JAWA - Annisa Salsabila Putri; Kalvin Edo Wahyudi (Journal Publicuho, 2024)
Corporate Social Responsibility (CSR) is a commitment given by companies or the business world to contribute to sustainable economic development, this focuses on economic, social and environmental. Therefore, one way to reduce the poverty rate is by requiring every company to carry out social responsibility, especially for people who live close to the company's environment. PT Pelabuhan Indonesia Regional III Sub Regional Java is one of the companies that carries out social responsibility as stated in Law no. 40 Article 74 concerning Limited Liability Companies. This article aims to find out how the Corporate Social Responsibility (CSR) program of PT Pelabuhan Indonesia (Persero) Regional III Sub Regional Java is implemented in the context of community empowerment which will be reviewed through George C. Edward III's four implementation models, namely: Communication, Resources (Resources), Dispositions (Dispositions), and Bureaucratic Structure (Bureaucratic Structure). The research method used is descriptive qualitative, with data collection techniques using observation, interviews and documentation. The results of this research are the implementation of the Corporate Social Responsibility (CSR) program with indicators of Communication, Disposition and Bureaucratic Structure which has been running well. Meanwhile, the Resource indicator has gone quite well.